2008
DOI: 10.1039/b802916d
|View full text |Cite
|
Sign up to set email alerts
|

Self-diffusion coefficients and shear viscosity of inverse power fluids: from hard- to soft-spheres

Abstract: Molecular dynamics computer simulation has been used to compute the self-diffusion coefficient, D, and shear viscosity, eta(s), of soft-sphere fluids, in which the particles interact through the soft-sphere or inverse power pair potential, phi(r) = epsilon(sigma/r)(n), where n measures the steepness or stiffness of the potential, and epsilon and sigma are a characteristic energy and distance, respectively. The simulations were carried out on monodisperse systems for a range of n values from the hard-sphere (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…Simple atomic systems studied for many years by computer simulations include the Lennard-Jones (LJ) pairpotential system, the hard-sphere system, the Yukawa (screened Coulomb) system, inverse power-law systems, etc [10][11][12][13][14]. Several molecular models are also simple in the sense that they have lines in the thermodynamic phase diagram, so-called isomorphs, along which the dynamics is invariant to a good approximation in suitably reduced units [15][16][17].…”
mentioning
confidence: 99%
“…Simple atomic systems studied for many years by computer simulations include the Lennard-Jones (LJ) pairpotential system, the hard-sphere system, the Yukawa (screened Coulomb) system, inverse power-law systems, etc [10][11][12][13][14]. Several molecular models are also simple in the sense that they have lines in the thermodynamic phase diagram, so-called isomorphs, along which the dynamics is invariant to a good approximation in suitably reduced units [15][16][17].…”
mentioning
confidence: 99%
“…This model has been investigated before, e.g. Hoover et al reported its phase behaviour [13], and more recently, Heyes et al studied the transport properties of fluids modelled with inverse power law interactions, from n = 4 up to the hard-sphere limit (n → ∞) [5]. The solvent was modelled with the stochastic rotation dynamics, or multi-particle collision dynamics method, first proposed by Malevanets and Kapral [14].…”
Section: Simulation Methodsmentioning
confidence: 99%
“…These studies focused on the dependence of the viscosity on the strain rate and the observation of shear thinning [2,3], as well as the rationalisation of the shear thinning in terms of the equilibrium structure of the fluid [4]. Additional studies investigated the dependence of the shear viscosity with the thermodynamic state, namely, density and pressure, considering different particle interactions [5]. Hydrodynamic interactions have also been studied using Stokesian dynamics [6], revealing the hydrodynamic origin of shear thickening.…”
Section: Introductionmentioning
confidence: 99%
“…The EXP pair potential has not been studied much on its own right, in fact even less than other purely repulsive pair potentials like the family of inverse-power law pair potentials [2][3][4][5][6][7][8][9]. In most cases, the exponential function appears as a term in mathematically more involved potentials, for instance: 1) giving the repulsive part of the Born-Meyer pair potential from 1932 [10] or in embedded-atom models of metals [11,12], 2) multiplied by a Coulomb term to give the Yukawa (screened Coulomb) potential [13,14], or 3) giving the attractive long-ranged part in a model that rigorously obeys the van der Waals equation of state in one dimension [15].…”
Section: Introductionmentioning
confidence: 99%